2022
DOI: 10.1186/s13561-022-00396-6
|View full text |Cite
|
Sign up to set email alerts
|

Does less working time improve life satisfaction? Evidence from European Social Survey

Abstract: Background Worktime is one of the main drivers of life satisfaction, and a balanced distribution of working hours and leisure hours directly impacts feelings of well-being. Based on previous studies, we seek to confirm this relationship in the European context and explore other potential driving forces of life satisfaction. Health condition as the mediating variable is also examined. Methods This article uses an ordered probit model to analyze the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 94 publications
1
3
0
2
Order By: Relevance
“…Of course, this will be re ected in their communication patterns with their patients, team, and colleagues [14]. The level of satisfaction will be affected not only by the working hours but by the number of shifts as well [15] which in congruence with this study results.…”
Section: Discussionsupporting
confidence: 72%
“…Of course, this will be re ected in their communication patterns with their patients, team, and colleagues [14]. The level of satisfaction will be affected not only by the working hours but by the number of shifts as well [15] which in congruence with this study results.…”
Section: Discussionsupporting
confidence: 72%
“…We found that many of the behaviors that conservatives engaged in more than liberals (e.g., leisure pursuits, physical activity) are those that prior research has linked to better individual wellbeing (40,60,61). Conversely, many of the behaviors liberals engaged in more than conservatives (e.g., working, domestic pursuits, social media use) are those that prior research has linked to worse wellbeing (40,62,63). Therefore, our work suggests there may be an underappreciated behavioral basis for why conservatives tend to be happier than liberals (13,(64)(65)(66).…”
Section: Substantive Methodological and Theoretical Contributionsmentioning
confidence: 72%
“…That is why many individuals who have many expectations to be fulfilled and cannot meet these expectations are faced with the negative feeling of lack of life satisfaction [ 88 ]. Thus, life satisfaction is one of the most critical factors that can affect migrants’ mental health and social relations, as the concepts of subjective well-being and life satisfaction have been stated by many scientists and researchers as the main goals of life and expectation of migrants, irrespective of their visa status [ 88 ]. Significantly, many factors may influence the subjective well-being and life satisfaction of internal and international migrants differently.…”
Section: Discussionmentioning
confidence: 99%